2006
DOI: 10.1038/sj.ijo.0803309
|View full text |Cite
|
Sign up to set email alerts
|

Additive benefits of long-chain n-3 polyunsaturated fatty acids and weight-loss in the management of cardiovascular disease risk in overweight hyperinsulinaemic women

Abstract: Background: Obesity, inflammation, insulin resistance and cardiovascular disease (CVD) risk are inter-related. Both weight-loss and long-chain n-3 polyunsaturated fatty acids (LC n-3 PUFA) are independently known to reduce metabolic risk, but the combined effects are unclear.Objective: This study examines whether addition of LC n-3 PUFA to a low fat/high carbohydrate weight-loss programme results in greater improvements in inflammation, insulin sensitivity and CVD risk, than weight-loss alone. Design: One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
171
4
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(195 citation statements)
references
References 50 publications
16
171
4
4
Order By: Relevance
“…The higher statistical power can explain our significant findings. Significant weight loss was achieved in our study, and it can be speculated that LC n-3 PUFA exert their positive health effects on insulin sensitivity best during weight loss; however, similar or greater amounts of weight loss were achieved in similar studies [34,35] that did not report significant effects of LC n-3 PUFA on insulin sensitivity. We cannot explain why endpoint fasting insulin and HOMA-IR values for the salmon group were not significantly different from those for the control group, despite the fact that salmon provided the highest dose of LC n-3 PUFA in our study.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…The higher statistical power can explain our significant findings. Significant weight loss was achieved in our study, and it can be speculated that LC n-3 PUFA exert their positive health effects on insulin sensitivity best during weight loss; however, similar or greater amounts of weight loss were achieved in similar studies [34,35] that did not report significant effects of LC n-3 PUFA on insulin sensitivity. We cannot explain why endpoint fasting insulin and HOMA-IR values for the salmon group were not significantly different from those for the control group, despite the fact that salmon provided the highest dose of LC n-3 PUFA in our study.…”
Section: Discussionsupporting
confidence: 39%
“…However, there were no independent effects of fish on glucose or insulin. A similar intervention study involving 116 overweight insulin-resistant women showed independent (from weight loss) effects of LC n-3 PUFA supplementation on triacylglycerol and adiponectin levels, but not insulin sensitivity [35]. The Kuopio, Aarhus, Naples, Wollongong and Uppsala (KANWU) study, a controlled multi-centre isoenergetic dietary intervention study focusing on dietary fat composition but not weight loss in 162 individuals, showed that decreasing dietary saturated fatty acid intake and increasing monounsaturated fatty acid intake improves insulin sensitivity, but no effect of fish oil supplementation on insulin sensitivity was found, despite reduced plasma triacylglycerol concentrations [36].…”
Section: Discussionmentioning
confidence: 89%
“…The fall in TG in the salmon group and the fish oil group is therefore in agreement with the extensive literature on the TG-lowering effects of LC n-3 PUFAs and results from recent trials, showing beneficial effects of LC n-3 PUFA supplementation on cardiovascular risk factors during weight loss. [6][7][8] However, TG-lowering effect of the lean cod diet shown in this study has not been seen previously in a human study. The different components of fish contributing to cardiovascular health have been assessed in the rat, where cod protein has been shown to lower hepatic TG concentration and TG secretion rate when compared with casein.…”
Section: Discussionmentioning
confidence: 69%
“…4,5 Long-chain n-3 poly-unsaturated fatty acids (LC n-3 PUFAs), given as supplements, have in recent trials been shown to have beneficial effects on cardiovascular disease risk factors as an additional therapy to calorie restriction in overweight and obese individuals. [6][7][8] The triacylglycerol (TG) lowering effects of n-3 fatty acids are well documented, 9 and the beneficial effects of fish intake seen on blood lipids in previous trials have primarily been attributed to the presence of n-3 fatty acids. The role of other seafood constituents, such as fish proteins, has been studied in animals.…”
Section: Introductionmentioning
confidence: 99%
“…3 g EPA and 2 . 9 g DHA (administered as EPAX 2050 TG; EPAX AS) in overweight patients who were simultaneously undertaking a weight-loss programme (75) . The induction of adiponectin could contribute to the beneficial effect of n-3 LC PUFA on systemic insulin sensitivity.…”
mentioning
confidence: 99%